Influence of Social Media on the Decision to Undergo a Cosmetic Procedure - Arab, Khalid; Barasain, Omar; Altaweel, Abdullah; Alkhayyal, Jawaher; Alshiha, Lulwah; Barasain, Rana; Alessa, Rania; Alshaalan, Hayfaa (Plastic and reconstructive surgery. Global open, 2019)
BACKGROUND:There is a rise of cosmetic procedures in Saudi Arabia. Social media have become a popular means of advertisements for cosmetic professional providers. There are currently no studies that determine the relationship between viewing cosmetic surgery advertisements and considering undergoing cosmetic procedures in female university students in Saudi Arabia. METHODS:A cross-sectional study was conducted using an online survey. This survey determined the use of social media, cosmetic-related accounts followed by the respondent, and attitudes toward advertising for cosmetic treatments on social media. It also determines the influence of these accounts on female university students to consider undergoing cosmetic treatments in the future. The survey was distributed on multiple social media platforms and by Email. RESULTS:Out of 816 completed questionnaires, 48.5% reported being influenced by social media to consider undergoing cosmetic procedures. Respondents (51.4%) follow plastic surgeons on social media (P < 0.001). The most common reported number of hours of social media use per day was >5 hours per day (53.2%; P < 0.026). Statistical significance was considered in relation to reporting being influenced by social media to consider undergoing cosmetic procedures in the future. CONCLUSIONS:Our findings revealed that viewing cosmetic surgery–related material on social media, spending longer hours on social media platforms, and having negative self-views when viewing social media are associated with an increased likelihood of considering undergoing cosmetic procedures in the future. Future studies using a validated questionnaire that assesses the likelihood of being influenced by social media to undergo cosmetic treatments are encouraged.